A Modern Survey of Tetralunata (Rhopalodiales, Bacillariophyta) Species and Their Distribution in Lake Toba, Indonesia - Ni Made Desi Swastiki; John Patrick Kociolek; Dian Hendrayanti (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Tetralunata is a genus of canal-bearing raphid diatoms (ordo Rhopalodiales) with the unique feature of cyanobacterial symbionts. A species assigned to the genus was originally reported and described from Lake Toba by Brun in 1891, and several species described by Hustedt in 1935 and 1937 under the name Denticula Kützing (1844) have also been transferred to Tetralunata. According to Hustedt, 14 species now in Tetralunata were originally found alive or as fossil forms. Firstly, this study aimed to reconfirm the presence of Tetralunata in Lake Toba after its first description more than 130 years ago. The second purpose was to examine Tetralunata habitats in Lake Toba, which were not described by Hustedt in his 1935 and 1937 reports. Samples were collected from various sites around the lake and observed using light microscopy after cleaning with hydrogen peroxide (H₂O₂) and potassium dichromate (K₂Cr₂O₇). As a result, 9 species of Tetralunata were found: T. amphicephala, T. angusta, T. costata, T. elongata, T. lanceolata, T. obtusa, T. pelagica, T. cf. robusta, and T. vanheurckii, indicating Tetralunata biodiversity in Lake Toba. Six species previously reported by Hustedt were not found in this study, while four species that had been reported as fossil forms were found alive in this study.